Chaya Plant Extract Jatropha tanjorensis: The Concepts of Bioremediation of Contaminated Soil Evaluation - Ukpaka Chukwuemeka Peter; Ikenyiri Patience Nna; Alhassan Monday Alkali (International Journal of Advance in Molecular Engineering, 2024)
This research was carried out to study the performance of sun-dried and room dried Chaya plant extract on the remediation of crude oil contaminated soil samples from Obele Community. The parameters under investigation were Total Petroleum Hydrocarbon degraded((TPHD), pH, amount of Nitrogen, Phosphate, and Potassium, Total organic carbon. Twenty-two (22) batch reactors were used for this research with each reactor containing 1kg of soils samples contaminated with 100ml of crude oil were treated with 20g, 40g, 60g, 80g, 100g of Chaya plant extract sun-dried (CPEL), Chaya plant extract dark (CPED), to each. The soil samples used for this research were loamy and sandy, the physiochemical properties of the soil samples used before and after were determined at the beginning and 84 days of the experiment. These physiochemical properties were electrical conductivity (EC), moisture content (MC), Total organic carbon (TOC), soil total organic matter (STOM), total nitrogen (TN) and phosphorus (P) in the soils increased after pollution. However, EC, MC, TOC, TOM, TN and P declined significantly with time after exposure to the treatment, while pH trend towards neutrality after the treatment. The rate of biodegradation of TPH was examined in every 14 days’ interval for 84 days, the results obtained shows a high performance of the plants extracts on all the soils samples with the sample on the loamy soil performing better when compared to the sand soil, however with relatively high degradation in remediate processed in the absent of direct sun light.
Keywords: Chaya plant extract; Jatropha tanjorensis; bioremediation; concepts; contaminated; evaluation; soil